Analisis Pemikiran Al-Kindi Dalam Bidang Filsafat - Mooduto, Maryam; Santalia, Indo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Al-Kindi is the first Muslim philosopher to construct Islamic philosophical thoughts in a systematic and clear way. Philosophical thoughts of Al-Kindi are reflection of doctrines that he received from classic Greece sources and the legacy of Neo-Platonic thoughts combined with Islamic faith. Al-Kindi opens the room of dialogue to combine philosophical doctrines and religion. Knowledge about God, according to Al-Kindi, is early philosophy or the first philosophy; philosophy that states al-Haqq as telos that will end the overall works of philosophy. Al-Kindi divides intelligence based on several stages as follows: active intelligence (intelligence that guarantees the ability of human beings to understand rational matters that needs external stimuli), actual intelligence (potential intelligence that escaped potential boundary when soul started to understand rational and abstract matters), and physical intelligence (intelligence that seriously comprehend rational matters and seeks to transform potential matter into actual thing)